2020
DOI: 10.1016/j.ebiom.2020.102632
|View full text |Cite
|
Sign up to set email alerts
|

Near infrared photoimmunotherapy targeting DLL3 for small cell lung cancer

Abstract: Background: Small cell lung cancer (SCLC) has a poor prognosis, and its treatment options are limited. Deltalike protein 3 (DLL3) is expressed specifically in SCLC and is considered a promising therapeutic target for patients with this disease. Rovalpituzumab tesirine (Rova-T) was the first antibody-drug conjugate targeting DLL3. Although Rova-T development was unfortunately terminated, DLL3 remains an ideal target for SCLC. Near infrared photoimmunotherapy (NIR-PIT) is a new form of cancer treatment that empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 42 publications
0
37
0
Order By: Relevance
“…In vivo experiments have confirmed that DLL3-overexpressing SCLC tumors are immediately destroyed upon NIR-light exposure. 37 Immunohistochemistry is used to assess DLL3 expression from SCLC biopsies and predict the effects of DLL3targeted agents; however, several practical limitations remain. 38 The application of immuno-positron emission tomography (immunoPET) can non-invasively provide real-time information regarding the status of in vivo DLL3 expression in tumors, facilitating the selection of patients for treatment with DLL3-targeted agents.…”
Section: Delta-like Ligands In Lung Cancermentioning
confidence: 99%
“…In vivo experiments have confirmed that DLL3-overexpressing SCLC tumors are immediately destroyed upon NIR-light exposure. 37 Immunohistochemistry is used to assess DLL3 expression from SCLC biopsies and predict the effects of DLL3targeted agents; however, several practical limitations remain. 38 The application of immuno-positron emission tomography (immunoPET) can non-invasively provide real-time information regarding the status of in vivo DLL3 expression in tumors, facilitating the selection of patients for treatment with DLL3-targeted agents.…”
Section: Delta-like Ligands In Lung Cancermentioning
confidence: 99%
“…PIT led to significant reductions in tumor volume in both the flank model and the pleural dissemination model 84 - 89 . Similarly, the delta-like protein 3 (DLL3) mAb rovalpituzumab was conjugated to IRDye 700DX to form rova-IR700, which decreased tumor burden markedly by PIT 90 . An anti-podoplanin antibody, NZ-1, was also synthesized with IRDye 700DX to treat a malignant pleural mesothelioma (MPM) model 74 .…”
Section: Photodynamic Immunotherapymentioning
confidence: 99%
“…We abbreviate IR700 conjugated to NZ-1 as NZ-1-IR700. The detection of binding of NZ-1-IR700 on PDPN was evaluated with immunoblot according to previous reports [21,29].…”
Section: Synthesis Of Ir700-conjugated Nz-1mentioning
confidence: 99%
“…Among the organs in the human body, the lung and thoracic cavity can most effectively transmit NIR-light, because it consists of a large amount of air [21][22][23]. Thus, MPM is a potentially good target for NIR-PIT.…”
Section: Introductionmentioning
confidence: 99%